EFFORTS TO IMPROVE SCIENCE LEARNING OUTCOMES THROUGH JIGSAW LEARNING MODEL IN CLASS IV SDN SUMBERJO - Dyah Rahayu Restiana Putri; Agung Setyawan (Citra Dharma Cindekia, 2022)
This study aims to determine how the jigsaw learning model can improve science learning outcomes in grade IV at SDN Sumberjo. This research is a classroom action research using Kurt Lewin's model which includes 4 stages, namely planning, action, observation, and reflection. Data on student learning outcomes and questionnaires were analyzed quantitatively while student observation data were analyzed qualitatively. The results showed in the first cycle the percentage of student learning outcomes the average value of the pre-test was 61.25% with classical completeness criteria in class 50%. Then the percentage of student learning outcomes the average score on the posttest increased by 77.5% with the classical completeness criteria in the class, namely 75%. Furthermore, in the second cycle of action, it can be seen from the percentage of student learning outcomes, the average pre-test score is 85% with classical completeness in the class of 87.5%. Then the percentage of student learning outcomes the average score on the post test also increased by 96.25% with the classical completeness criteria in the class, namely 100%. The results of the analysis can be concluded that the jigsaw learning model is able to improve students' science learning outcomes.